The clinical characteristics, treatment and prognosis differences between occipital brain tumors with venous flow obstruction and occipital brain tumors without venous flow obstruction - Ofira Zloto; Mati Bakon; Ruth Huna-Baron (BMC Ophthalmology)
Abstract Objective To examine the clinical characteristics and prognosis of occipital tumors that mimic Pseudotumor cerebri (PTC) at presentation due to venous flow obstruction compared to occipital tumors that do not cause venous flow obstruction. Methods The medical records of all patients who presented with increased intracranial pressure symptoms and occipital tumors were retrospectively reviewed. The control group included, an age matched group of patients with occipital tumor who presented due to homonymous visual disturbances, visual hallucinations or incidental homonymous visual field defect but without symptoms of increased intracranial pressure at presentation. Data regarding demographics, ocular presenting symptoms and signs, neurological sings, diagnosis, treatment and prognosis were collected. Results At the end of follow up, None of the study group patients, with the exception of one who developed optic disc atrophy and visual deterioration, had visual complaints at the end of follow-up. In the control group, 3 patients had deterioration in the visual field at the end of follow up. Two patients, from the study group, died while in the control group, all patients were alive at the end of follow- up. Conclusions Patients with occipital tumors may present with symptoms similar to PTC secondary to venous drainage obstruction. Therefore, it is important in patients with PTC symptoms and occipital tumor to preform Magnetic-Resonance-Venography or Computed-Tomography-Venography as well. Most of the patients needed surgical intervention in addition to medical treatment in order to preserve visual functions. Probably the early treatment to this group brought to good visual prognosis that was not different from the group without venous drainage obstruction. Therefore, early diagnosis and prompt multi-disciplinary treatment may lead to better results in cases of occipital tumors with venous drainage obstruction.